Corporate social responsibility and sustainable development: A literature review and future research directions - Tran, Dang Khoa (Edelweiss Applied Science and Technology, 2025)
This study aims to provide readers with a comprehensive literature review of studies that mention corporate social responsibility (CSR) and sustainable development. Given the broad scope of this topic and the large volume of related documents, bibliometric analysis was employed. Data were collected in January 2025 from the Web of Science database, comprising 4,823 documents. Performance analysis was conducted to illustrate publication trends over the years, as well as contributions by authors, countries, and research areas. The study utilized co-citation and bibliographic coupling analyses to explore foundational research and thematic developments from past to present. Additionally, co-keyword analysis was performed to identify emerging research directions for the future. The results indicated a need for increased research focus on the African context. Areas recommended for further investigation include energy fuels, agriculture, geography, transportation, and mineral processing in mining. Key issues requiring additional research attention encompass the relationship between CSR and corporate financial performance, characteristics of the board of directors, green supply chains, and strategic CSR initiatives. The study identified several future-oriented themes, such as ESG performance, green innovation, green finance, pro-environmental behavior, environmental sustainability, product innovation, and board diversity, which are expected to shape ongoing research in this field.